2004
DOI: 10.1097/01.wcb.0000145666.68576.71
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Toll-like Receptor and Cytokine Signaling—A Unifying Theme in Ischemic Tolerance

Abstract: Summary:Cerebral ischemia triggers acute inflammation, which exacerbates primary brain damage. Activation of the innate immune system is an important component of this inflammatory response. Inflammation occurs through the action of proinflammatory cytokines, such as TNF, IL-1␤ and IL-6, that alter blood flow and increase vascular permeability, thus leading to secondary ischemia and accumulation of immune cells in the brain. Production of these cytokines is initiated by signaling through Toll-like receptors (T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
210
0
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 240 publications
(217 citation statements)
references
References 173 publications
(153 reference statements)
5
210
0
2
Order By: Relevance
“…The TLR family includes receptors for bacterial cell wall/membrane components such as lipotechoic acid (TLR2), peptidoglycan (TLR2), and LPS (TLR4) [16]. Activation of TLRs by endogenous ligands, also known as danger-associated molecular patterns (DAMPs), released from ischemia-injured cerebral vasculature and parenchyma is a possible mechanism for initiation of inflammatory responses in stroke [2,61]. A number of putative DAMPs, including heat shock proteins (HSPs) [62,63], especially HSP70 [64] and HSP60 [62]both will activate TLRs-have been identified in the brain.…”
Section: Molecular Mediators Of Preconditioningmentioning
confidence: 99%
“…The TLR family includes receptors for bacterial cell wall/membrane components such as lipotechoic acid (TLR2), peptidoglycan (TLR2), and LPS (TLR4) [16]. Activation of TLRs by endogenous ligands, also known as danger-associated molecular patterns (DAMPs), released from ischemia-injured cerebral vasculature and parenchyma is a possible mechanism for initiation of inflammatory responses in stroke [2,61]. A number of putative DAMPs, including heat shock proteins (HSPs) [62,63], especially HSP70 [64] and HSP60 [62]both will activate TLRs-have been identified in the brain.…”
Section: Molecular Mediators Of Preconditioningmentioning
confidence: 99%
“…A recent study has also shown a role of TLR3 in the recognition of RNA released by dying or dead cells (11,55,56). In this case, it was demonstrated that secondary structure creating hairpin loops within the mRNA was responsible for TLR3 activation.…”
Section: Discussionmentioning
confidence: 91%
“…Cytokines such as interleukin-1 (IL-1), and TNF-α are important mediators of the inflammatory reactions seen in cerebral ischemia. The importance of the cytokine system in the setting of ischemia was emphasized by Kariko et al [28] . TNF-α is one of the pro-inflammatory cytokines and is expressed in the ischemic brain.…”
Section: Inflammatory Cytokinesmentioning
confidence: 99%